EFL Students’ Perspective on the Use of Quizizz as Online Learning Media During COVID-19 Pandemic - Naomi Nirwasita Dewi; Irma Windy Astuti (Indonesia Approach Education, 2021)
The purpose of this research is to investigate and describe the students' perspectives on the use of Quizizz in their online language learning during the COVID-19 Pandemic. This research was done using a descriptive qualitative research design conducted at a public university in Central Java. Furthermore, there were two participants in this research, male and female. In addition, the data were collected from the interview as the main source for this research. Additionally, thematic analysis was used by the researcher to analyze the data findings. This research revealed that students had a positive view of the use of Quizizz as learning media. It was found that Quizizz became one of the online learning media that helped students during online learning. Moreover, the findings showed Quizizz keeps students motivated, makes them pay attention during online learning, and also affects students' concentration during their online learning.